2014
DOI: 10.1111/cdev.12242
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Trajectory of Socioeconomic Disparity in Working Memory: Parental and Neighborhood Factors

Abstract: Working memory (WM) is positively correlated with socioeconomic status (SES). It is not clear, however, if SES predicts the rate of WM development over time nor whether SES effects are specific to family rather than neighborhood SES. A community sample of children (n = 316) enrolled between ages 10 and 13 completed four annual assessments of WM. Lower parental education, but not neighborhood disadvantage, was associated with worse WM performance. Neither measure of SES was associated with the rate of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 71 publications
14
74
0
1
Order By: Relevance
“…Allen, Baddeley, & Hitch, 2006, 2014. This extends limited previous work with children using different visual stimuli (Burnett Heyes et al, 2012;Hitch et al 1988;Pickering et al 1998) to the current task and stimulus sets.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Allen, Baddeley, & Hitch, 2006, 2014. This extends limited previous work with children using different visual stimuli (Burnett Heyes et al, 2012;Hitch et al 1988;Pickering et al 1998) to the current task and stimulus sets.…”
Section: Discussionsupporting
confidence: 71%
“…This allows the separation of different mechanisms that contribute to visual WM. A robust finding from such analysis is a large recency effect for the final item in a list (Allen, Baddeley, & Hitch, 2006, 2014Gorgoraptis, Catalao, Bays, & Husain, 2011;Hu et al, 2014Hu et al, , 2016. Additionally, performance on the final item in a sequence is vulnerable to suffix interference (where a to-be-ignored item drawn from the stimulus set is briefly presented following the final item in a sequence), yet is largely unaffected by cognitive load Hu et al, 2014Hu et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the environmental factors, our data showed that SES and HLE are directly associated with language, replicating previous findings (Farah et al, 2006;Hackman & Farah, 2009;Hart & Risley, 1992;Hoff & Tian, 2005;McKean et al, 2015;Noble et al, 2007;Roberts et al, 2005;Sénéchal & LeFevre, 2014;Wood, 2002). Moreover, consistently with the literature across kindergartners, first graders, and preadolescents (Evans & Schamberg, 2009;Farah et al, 2006;Hackman et al, 2014;Sarsour et al, 2011;Waber et al, 2007), disadvantaged SES was related to impaired temporary memory.…”
Section: The Role Of Ses and Hlesupporting
confidence: 91%
“…For example, SES in children attending primary school accounted for 5.5% of the variance in vWM (Noble et al, 2007). Similar correlations between SES and vWM have been shown in middle childhood (Sarsour et al, 2011) and in adolescence (Hackman et al, 2014;Waber et al, 2007), suggesting enduring effects.…”
Section: Memory As a Mediator Between Environmental And Biological Fasupporting
confidence: 52%
See 1 more Smart Citation